2019
DOI: 10.2147/ott.s197676
|View full text |Cite
|
Sign up to set email alerts
|

<p>Identification and validation of an individualized autophagy-clinical prognostic index in bladder cancer patients</p>

Abstract: Purpose: Autophagy is a major catabolic system by which eukaryotic cells undergo self-degradation of damaged, defective, or unwanted intracellular components. An abnormal autophagic level is implicated in the pathogenesis of multiple diseases, including cancers. The aim of this study is to explore the prognostic value of autophagy in bladder cancer (BC), which is a major cause of cancer-related death globally. Patients and methods: First, 27 differentially expressed autophagy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 42 publications
1
44
0
Order By: Relevance
“…TCGA is an open-access database that uses a genome-wide approach to reveal the genetic characteristics of cancers. Many studies on cancers such as BLCA have screened diagnostic and prognostic biomarkers using TCGA [18][19][20]. Patient subgroups with different treatment response and prognosis can also be identified using TCGA.…”
Section: Discussionmentioning
confidence: 99%
“…TCGA is an open-access database that uses a genome-wide approach to reveal the genetic characteristics of cancers. Many studies on cancers such as BLCA have screened diagnostic and prognostic biomarkers using TCGA [18][19][20]. Patient subgroups with different treatment response and prognosis can also be identified using TCGA.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to explore alternative methods for diagnosis and accurate postoperative tumour staging. Page 2 of 12 Wang et al J Transl Med (2020) 18:149 Autophagy is considered a vital catabolic process within eukaryotic cells, allowing lysosomes to degrade damaged, senescent, or nonfunctional proteins and organelles [4,5]. Early studies have reported that autophagy is involved in many pathophysiological processes such as immune responses, inflammation, neurodegenerative diseases, tumourigenesis and cancer progression [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, autophagy is considered as a "double-edged sword", since it not only inhibits tumor progression by depriving cells of nutrients and energy, but also promotes tumor progression by conferring cells with nutrients and energy [19,20]. in predicting overall survival of bladder cancer [22]. However, the prognostic signi cance of autophagy genes in endometrial cancer has not been reported.…”
Section: Discussionmentioning
confidence: 99%